Risk factors associated with treatment default in pulmonary tuberculosis patients in Tshwane, Gauteng : case control study - Moodley, Saiendhra Vasudevan (University of Pretoria, 2021)
Dissertation (MMed (Public health Medicine))--University of Pretoria, 2013.